2021
DOI: 10.1002/nop2.868
|View full text |Cite
|
Sign up to set email alerts
|

A survey of nurses' experience integrating oncology clinical and academic worlds

Abstract: Historically, a gap between theory and practice has existed in the nursing profession, while, at the same time, academic institutions have actively sought to recruit nurses from practice into academic roles (Nardi & Gyurko, 2013). For nurses completing graduate education through Master's or Doctoral programs, the employment options are often situated in either a clinical or academic context, with few roles available that bridge both environments (Gibson, 2019). This often creates challenges for nurses striving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…and clinical roles in nursing. However, in one qualitative survey study by Haase et al (2021), clinical nurses enrolled in graduate studies reported being better equipped to shape and improve the healthcare system, improve patient care, and grow their knowledge in the oncology nursing discipline. Clinical nurses also described how their understanding of research and the effect it can have on current practices shaped how they educate others.…”
Section: Impactmentioning
confidence: 99%
See 4 more Smart Citations
“…and clinical roles in nursing. However, in one qualitative survey study by Haase et al (2021), clinical nurses enrolled in graduate studies reported being better equipped to shape and improve the healthcare system, improve patient care, and grow their knowledge in the oncology nursing discipline. Clinical nurses also described how their understanding of research and the effect it can have on current practices shaped how they educate others.…”
Section: Impactmentioning
confidence: 99%
“…They also believed that maintaining a synergy with clinical practice enhanced the future dissemination and uptake of their research into clinical practice in the long-term. Haase et al (2021) concluded that there is growing evidence that integrating clinical practice into academic roles has the potential to enhance patient care, improve the healthcare system, and advance the field of oncology nursing in the long term.…”
Section: Impactmentioning
confidence: 99%
See 3 more Smart Citations